KETERAMPILAN KEPALA SEKOLAH DALAM PROSES PENGAMBILAN KEPUTUSAN DI MTS NURUL AMAL - Rahmawati, Ima; Suhendar, Ratna Triani (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
This study aims to examine the skills of school principals in the decision-making process at MTs Nurul Amal, as well as analyze the factors that affect them. The approach used is qualitative with a case study type, involving interviews, observations, and documentation as data collection techniques. The results of the study showed that the principal has good analytical skills, participatory communication, and the ability to manage conflicts that arise in schools. In addition, the principal considers factors such as leadership experience, organizational culture, and Islamic values in decision-making. This study concludes that the principal's skills in decision-making play an important role in improving the quality of managerial and education in MTs Nurul Amal. The research also provides suggestions for the development of principals' skills in technology- and data-driven decision-making.